Epistemologi Sufi Healing di Tarekat Qadiriyyah Naqsyabandiyyah Pondok Pesantren Suryalaya - Teten Jalaludin Hayat (UPT Pusat Studi Aswaja UNISNU Jepara, 2023)
AbstractThis study aims to explain epistemologically about Sufi healing in the Qadiriyyah Naqsyabandiiyyah Sufi order of Suryalaya. The research method used is qualitative and epistemological through a content analysis knife, so that conclusions can be obtained with practical qualities for adherents of Sufi healing. The epistemological process of Sufi healing is carried out through the most important healing tool (akbar) and provides the strongest psychological influence (asyadd ta'tsiran), namely dhikr jahr. Dhikr jahr is nafy (negation) and itsbat (affirmation) function, which work in tandem to produce its axiological fruit, namely clean and stable mind (tsabat). In the process of nafy and itsbat, at times the mind will experience a state of trance (half consciousness), the inner warehouse is wide open, so that the inner impurities (al-muhaddatsat, hadith al-nafs, mind defilements) will come out on their own and spill over into the sky of the mind. After that, for full healing, the certain method of consciousness power is carried out through nazhr al-fana' (missing sight). If the process of nazhr al-fana' is successful, the mind becomes cleaner and calmer, the view becomes brighter. Thus, the epistemological process of Sufi healing through dhikr jahr was successfully carried out by a healer.Keywords: Zikir, Epistemologi, Sufi Healing, TQN Suryalaya.AbstrakPenelitian ini ditujukan untuk menjelaskan secara epistemologis tentang sufi healing di Tarekat Qadiriyyah Naqsyabandiiyyah Pondok Pesantren Suryalaya. Metode penelitian yang digunakan bersifat kualitatif dan epistemologis melalui pisau analisis isi, sehingga bisa diperoleh kesimpulan dengan kualitas praktis bagi penganut sufi healing. Proses epistemologis sufi healing dilakukan melalui alat healing yang paling utama (akbar) dan memberikan pengaruh kejiwaan paling kuat (asyadd ta’tsiran), yaitu dzikir jahr. Dzikir jahr bersifat nafy (negasi) dan itsbat (afirmasi), yang berkerja secara beriringan untuk melahirkan buah aksiologisnya, yaitu bersih dan tetapnya batin (tsabat). Di dalam proses nafy dan itbsat, pada masanya batin akan mengalami kondisi trans (half consciousness), gudang batin terbuka lebar, sehingga kotoran batin (al-muhaddatsat, hadits al-nafs, mind defilements) akan berkeluaran sendiri dan tumpah di langit pikiran. Setelah itu, untuk meng-healing secara penuh, dilakukan metode kasadaran melalui nazhr al-fana’ (pandangan lenyap). Bila berhasilnya proses nazhr al-fana’, batin menjadi lebih bersih dan tenang, pandangan menjadi lebih terang. Dengan demikian, proses epistemologis sufi healing melalui dzikir jahr berhasil dilakuan oleh seorang healer.Kata Kunci: Dzikir, Epistemologi, Sufi Healing, TQN Suryalaya.